Odpowiedzi

2010-03-17T19:45:57+01:00
A)x-1pzez 3 -x-2przez 2=2x-5przez 6 /*6 = 2x-2-3x+6=2x-5
-x+4=2x-5
-3x=-9/:(-3)
x=3
b)2x-1przez 4+x-1przez 2=5x-9przez 4/*4
2x-1+2x-2=5x-9
4x-5x=-6
-x=-6/*(-1)
x=6
c)x+6przez2-5+xprzez 3=2-xprzez 6/*6
3x+18-10-2x=2-x
2x=-6/:2
x=-3
d)x+4przez4-2x-1przez 2 =x+2przez 4/*4
x+4-4x+2=x+2
-4x=-4 /: (-4)
x=1
2010-03-17T19:52:24+01:00
A)x-1pzez 3 -x-2przez 2=2x-5przez 6
x-1/3-x-2/2=2x-5/6
x-x-2x=-5/6+2/2+1/3
-2x=-5/6+6/6+2/6
-2x=3/6/*6
-12x=3/:(-12)
x=3/12
x=1/4
b)2x-1przez 4+x-1przez 2=5x-9przez 4
2x-1/4+x-1/2=5x-9/4
2x+x-5x=-9/4+1/2+1/4
-2x=-9/4+2/4+1/4
-2x=-6/4/*4
-8x=-6/:(-8)
x=3/4
c)x+6przez2-5+xprzez 3=2-xprzez 6
x+6/2-5+x/3=2-x/6
x+x/3+x/6=2+5-6/2 /*6
6x+2x+x=12+30-18
9x=24 /:9
x=2 6/9
x=2 2/3
d)x+4przez4-2x-1przez 2 =x+2przez 4
x+4/4-2x-1/2=x+2/4
x-2x-x=2/4+1/2-4/4
-2x=2/4+2/4-4/4
-2x=0/:(-2)
x=0

hehe mam nadzieje że pomogłam i że dobrze wszystko obliczyłam ;P



1 5 1